2018
DOI: 10.14419/ijet.v7i4.36.24211
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Poetry Enhances Speaking Skills – an Analysis Based on Select Poems

Abstract: English has become the medium of all relevant social interactions, discussions in all circumstances globally because of its numerous functions and preferences over several other languages. Language is the primary source of communication. It helps to exchange ideas and thoughts. The language skills, though not in proper way, are acquired at school level through the constituents of English Literature such as poetry, grammar and prose. This paper focuses how teaching poetry enhances the language skills of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 3 publications
0
13
0
1
Order By: Relevance
“…As students read the novels and short stories, they not only increase their vocabulary (Scientific Learning Corporation, 2008; Pikulski and Templeton, 2004), they also learn how language is used for communicative and aesthetic purposes. Deepa and Ilankumaran (2018) attest to the relevance of literature to the enhancement of communication skills. Also, literature could help learners develop critical and creative thinking skills.…”
Section: Introductionmentioning
confidence: 90%
“…As students read the novels and short stories, they not only increase their vocabulary (Scientific Learning Corporation, 2008; Pikulski and Templeton, 2004), they also learn how language is used for communicative and aesthetic purposes. Deepa and Ilankumaran (2018) attest to the relevance of literature to the enhancement of communication skills. Also, literature could help learners develop critical and creative thinking skills.…”
Section: Introductionmentioning
confidence: 90%
“…Liao (2017) also found that the students learn about composing better sentence structures through poetry presented in the target language. The use of poetry provides a platform for students to learn about sentence formation and syntax in the target language (Deepa & Ilankumaran, 2018). Deepa & Ilankumaran (2018) found that students who were taught using poetry is able to compose correct sentences in English and it has good coherence.…”
Section: Grammarmentioning
confidence: 99%
“…Moreover, Deepa & Ilankumaran (2018) presume that through poetry students can gain beautiful and romantic words which is a good social capital for practicing their communicative competence to their special relationship. In other words, it can be proper for maintaining their communication with their lovers, friends, etc.…”
Section: Types Of Literary Work Effectively Used By Teacher To Enhanc...mentioning
confidence: 99%